Functional analysis of zona pellucida domain protein Dusky in Tribolium castaneum. (8th July 2021) - Li, Chengjun; Yang, Liu; Wang, Youwei; Du, Huanyu; Zhang, Jiangyan; Lu, Yaoyao; Li, Bin; Chen, Keping
Abstract: The zona pellucida domain protein Dusky (Dy) plays a vital role in wing morphogenesis in insects, but little information on its function has been reported. In this study, we found that dy regulated wing cell size, larval and pupal duration, and the metabolism of amino acid and 20‐hydroxyecdysone in Tribolium castaneum . Using RNA‐seq, 413 differentially expressed genes were identified between physiological buffer‐injected and dy ‐double‐stranded RNA‐treated larvae, including 88 downregulated genes and 325 upregulated genes. Among these genes, dy knockdown increased CYP18A1 expression to elevate the 26‐hydroxylation of 20‐hydroxyecdysone, which ultimately led to growth defects in wing cells. Silencing of dy upregulated the transcription of genes encoding tyrosine aminotransferase, 4‐hydroxyphenylpyruvate dioxygenase, homogentisate 1, 2‐dioxygenase, and Pale to promote the catabolism of tyrosine and phenylalanine, which eventually reduced amino acid content. Furthermore, dy knockdown upregulated 4E‐BP expression, and 4E‐BP silencing partially phenocopied dy RNA interference‐mediated wing morphogenesis. These results suggest that Dy controls 20‐hydroxyecdysone and amino acid metabolism to regulate wing morphogenesis in the insect. Graphical Abstract: Normally, Dy inhibits amino acid metabolism by reducing the expression of TAT, pale, Hpd, and Hgo, and eventually downregulates 4E‐BP level. Additionally, Dy activates ftz‐f1 transcription but decreases CYP18A1 transcription to elevate 20E titer in insects. Dy also modulates the metabolism of amino acid and 20E to control wing morphogenesis.